Co-evolution of groups and opinions in an agent-based model - Duncan Cassells; Antoine Vendeville; Lionel Tabourier; Pedro Ramaciotti (PLoS ONE, 2025)
This study explores a model for the co-evolution of opinions and groups, related to opinion polarization and group identity in opinion dynamics. While traditional models focus on pairwise interactions, we incorporate the notion of groups thereby allowing agents to identify other agents as in-group or out-group. By modifying key parameters we examine how understanding interactions as in-group or out-group affects the convergence or divergence of opinions. Our findings reveal that attitude towards out-group plays a leading role in the polarization of such systems, while in-group interactions can temper extreme opinion shifts or even fragment groups. This model offers an understanding of the complex interplay between group identification and polarization, providing a contribution to ongoing debates about segregation and sectarianism in public and private spheres.